Mitigation of denial of service attacks in software-defined-cognitive radio network using software-defined-cognitive radio shield - Lebepe, Mampuele (My University, 2023)
A ground-breaking approach to managing network resources is provided by softwaredefined networks that solve a number of management-related concerns. A novel paradigm called Cognitive Radio Networks (CRN) was developed to circumvent spectrum limitations. Methods for efficient dynamic spectrum access are employed. CRN allows secondary unlicensed users to take advantage of the licensed spectrum without interfering with authorized users. Security breaches on these networks are unavoidable. Network security planning is the first step in network defence. This study develops a strategy for software-defined cognitive radio networks that detect and counteract denial of service (DoS) attacks. We develop an intrusion detection system (IDS) to research the consequences of DoS attacks and mitigate DoS attacks in software-defined cognitive radio networks. The IDS is software based and is connected to the software-defined cognitive radio network's controller. We focus on the detection time, or the amount of time it takes to realize an attack has occurred, the payload, or the portion of malware the attacker wants the victim to receive, the jitter, or the variance in the time delay when a signal is transmitted and when it is received over a network connection, and the packet drop rate, or the number of packets lost during an attack. The round trip time and throughput indicate how quickly packets are transmitted during an attack. To generate the findings and compare them to existing schemes, we used NetSim which was installed on the Windows 10 Operating System. We proposed a scheme that detects and mitigates DoS attacks which performed well in terms of the jitter, throughput, detection time, round trip time, and packet drop rate. We compared our scheme to the SDN-Guard. Our scheme achieved less throughput, packet drop rate and round-trip time. Our scheme achieved faster detection time and lower jitter. The payload of our scheme was also less compared to the SDN-Guard
Thesis (M.Sc.) -- University of Limpopo, 2023
Keywords: Managing network resources; Software defined networks; Cognitive Radio Networks; Cyberterrorism; Cognitive radio networks -- South Africa -- Limpopo; Computer system failures -- South Africa -- Limpopo Province; Radio cognitive -- South Africa -- Limpopo Province; Denial of service attacks